Mesenchymal stem cell-derived secretome accelerates third-degree burn wound healing: Effects on proliferation, angiogenesis, and fibrosis regulation - Dirja, Bayu T.; Putra, Agung; Amalina, Nur D. (Narra J, 2025)
Mesenchymal stem cell-derived secretome (MSC-derived secretome) has shown promise in regenerative medicine; however, research specifically evaluating its efficacy in third-degree burn wounds remains scarce. The aim of this study was to investigate the effects of MSC-derived secretome on cellular proliferation, angiogenesis, myofibroblast activity, and collagen synthesis in a third-degree burn wound model. A total of 20 Wistar rats were randomly assigned to four groups: a healthy control group, a negative control group with untreated third-degree burn wounds, and two treatment groups receiving MSC-derived secretome at doses of 100 µL and 200 µL for 14 days. The wound healing was assessed 14 days post-treatment. Proliferating cell nuclear antigen (PCNA) protein expression was quantified via Western blot to assess cell proliferation; vascular endothelial growth factor (VEGF) gene expression was analyzed using quantitative reverse transcription polymerase chain reaction (qRT-PCR) to examine angiogenesis; alpha-smooth muscle actin (α-SMA) expression was assessed through immunohistochemistry to evaluate myofibroblast activity; and collagen density was measured using Masson's trichrome staining to determine tissue remodeling.  Our data indicated that MSC-derived secretome treatment significantly enhanced multiple aspects of the healing process in a dose-dependent manner. PCNA expression increased by 2.8-fold in the 200 µL MSC-derived secretome group compared to the negative control (p<0.05). VEGF gene expression was upregulated by 2.14-fold in the 200 µL secretome group compared to the negative control (p<0.05). α-SMA protein expression increased by 12.67% in the 200 µL secretome group, while collagen density demonstrated the most pronounced improvement at the 200 µL dose, reaching an increase of 81.26% (p<0.05). In conclusion, MSC-derived secretome significantly accelerates burn wound healing by promoting cell proliferation, enhancing angiogenesis, and increasing collagen synthesis while modulating myofibroblast activity. This highlights the potential of MSC-derived secretome as a therapeutic option for optimizing burn wound repair and reducing fibrotic complications.